Thromboprofilaxys With Fondaparinux vs. Enoxaparin in Hospitalized COVID-19 Patients: A Multicenter Italian Observational Study - Russo, Vincenzo; Cardillo, Giuseppe; Viggiano, Giuseppe Vito; Mangiacapra, Sara; Cavalli, Antonella; Fontanella, Andrea; Agrusta, Federica; Bellizzi, Annamaria; Amitrano, Maria; Iannuzzo, Mariateresa; Sacco, Clara; Lodigiani, Corrado; et al. (Frontiers in Medicine, 2020)
Importance: The use of anticoagulant therapy with heparins decreased mortality in hospitalized patients with severe coronavirus disease 2019 (COVID-19). Even if enoxaparin and fondaparinux have the same clinical indication for venous thromboembolism (VTE) prevention; to date, there are no data about the use of fondaparinux in terms of safety, effectiveness, and impact on clinical prognosis among COVID-19 patients. Objective: To evaluate the safety, effectiveness, and clinical impact of VTE prophylaxis with fondaparinux and enoxaparin among COVID-19 patients hospitalized in internal medicine units. Design, Setting, and Participants: This was a retrospective multicenter observation study, including consecutive symptomatic patients with laboratory-proven COVID-19 admitted to internal medicine units of five Italian hospitals from 15th February to 15th March 2020. Main Outcomes and Measures: The primary safety outcome was the composite of major bleeding and clinically relevant non-major bleeding; the primary effectiveness outcome was the composite of all events classified as pulmonary embolism and deep venous thrombosis. The secondary effectiveness outcome included acute respiratory distress syndrome and all-cause death. Results: Among 120 COVID-19 patients enrolled in the study, 74 were taking enoxaparin (4,000 or 6,000 units/day) and 46 fondaparinux (2.5 units/day). No statistically significant difference in demographic and laboratory and clinical characteristics between the two groups has been shown. During a median follow-up of 32 (interquartile range: 14–51) days, the cumulative incidence rates of VTE and bleeding events on pharmacological thromboprophylaxis with heparins were 19% and 8%, respectively. The incidence of both VTE (6.5 vs. 13.5%; P = 0.36) and bleeding events (6.5 vs. 4.1%; P = 0.68) did not show a significant difference between COVID-19 patients on fondaparinux compared with those on enoxaparin therapy. The regression model for the risk of outcome events according to different VTE prophylaxis drugs did not show significant differences. Conclusions and Relevance: Although these results need confirmation by prospective studies including a larger population, our study provides preliminary evidence of a safe and efficacy use of fondaparinux for VTE prophylaxis in hospitalized COVID-19 patients.